2009
DOI: 10.1051/fruits/2009030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different scion-rootstock combinations on vigor, tree size, yield and fruit quality of three Iranian cultivars of pomegranate

Abstract: Effects of different scion-rootstock combinations on vigor, tree size, yield and fruit quality of three Iranian cultivars of pomegranate. Abstract-Introduction. Probably because pomegranate trees are established in orchards as own-rooted plants, there are no studies regarding scion-rootstock combination effects on growth, tree size, yield and fruit quality of this fruit tree. Thus, the main aims of our experiment were to study the effects of some pomegranate rootstocks on growth and yield characteristics of Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 5 publications
4
6
0
1
Order By: Relevance
“…This finding is in agreement with Vazifeshenas [17] who demonstrated that specific rootstock significantly affected growth, yield and fruit quality of pomegranate. Growth indeed was significant amongst the rootstocks with JX1/9 × JX1/11 * B1/142 × B1/151 exhibiting high vigor with respect to the other stocks.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in agreement with Vazifeshenas [17] who demonstrated that specific rootstock significantly affected growth, yield and fruit quality of pomegranate. Growth indeed was significant amongst the rootstocks with JX1/9 × JX1/11 * B1/142 × B1/151 exhibiting high vigor with respect to the other stocks.…”
Section: Discussionsupporting
confidence: 82%
“…Percentage success of grafting and scion growth confirmed profound interaction between rootstock and scion. This is because scion JB1 which performed relatively poor in experiment I seemed to have performed much better with specific rootstock in experiment II than the unselected stocks in experiment I. Vazifeshenas [17] observed a similar trend in pomegranate and reported that how the rootstock controls grafting success and scion growth is not fully understood, however, Kamboj and Quinlan [18] explained that hormones are involved in the control of scion growth, since they found a higher concentration of cytokinin in root exudates from vigorous rootstocks than from dwarfing ones. Moreover, they also showed a lower ratio of Abscisic Acid (ABA) to Indole Acetic Acid (IAA) in vigorous rootstocks compared to dwarf rootstocks.…”
Section: Discussionmentioning
confidence: 98%
“…For peach and nectarine based rootstocks, vigor induction has been associated with hormonal relationships [19] and hydraulic conductance of roots and stems [18,20]. It was suggested that hormones may be involved to control scion growth, and a higher concentration of cytokinin was found in root exudates from vigorous rootstocks than from dwarfing ones [21]. Motisi et al [20] reported lower tree stem water potential and lower hydraulic conductivity on dwarfing rootstocks than on vigorous rootstocks (such as 'GF677').…”
Section: Vegetative Growthmentioning
confidence: 99%
“…Sobressaindo de outras técnicas de propagação vegetativa, como a estaquia, por permitir a utilização de um porta-enxerto com alto vigor que favorece rápido crescimento e desenvolvimento da romãzeira 'Wonderful' que ainda está sendo foco de estudo na região do semiárido brasileiro. Com isto, a utilização de porta-enxerto vigoroso pode auxiliar na maior tolerância à salinidade do solo (Picchioni et al, 1990) e também auxilia na maior absorção nutrientes em solos de baixa fertilidade (Vazifeshenas et al, 2009).…”
Section: Introductionunclassified